A phase II clinical trial of 6-mercaptopurine (6MP) and methotrexate in patients with BRCA defective tumours: a study protocol - Nicum, S; Roberts, C; Boyle, L; Kopijasz, S; Gourley, C; Hall, M; Montes, A; Poole, C; Collins, L; Schuh, A; Dutton, S (BioMed Central, 2014)
Background BRCA1 and BRCA2 genes are critical in homologous recombination DNA repair and have been implicated in familial breast and ovarian cancer tumorigenesis. Tumour cells with these mutations demonstrate increased sensitivity to cisplatin and poly (ADP-ribose) polymerase (PARP) inhibitors. 6MP was identified in a screen for novel drugs and found to selectively kill BRCA-defective cells in a xenograft model as effectively as the PARP inhibitor AGO14699, even after these cells had acquired resistance to a PARP inhibitor or cisplatin. Exploiting the genetic basis of these tumours enables us to develop a more tailored approach to therapy for patients with BRCA mutated cancers.